Pembelajaran Bahasa Arab dan Dinamika Wacana Bahasa: Studi Komparasi Teori Al-Sulūkiyyah dan Al-ʽAqliyyah antara Teks dan Konteks - Midi HS Midi HS (Aphorisme: Journal of Arabic Language, Literature, and Education, 2020)
Learning is an aid given by educators to enable the process of acquisition of knowledge and knowledge, mastery of skills and character, as well as the formation of students' attitudes and self-confidence. Where as Arabic is a discipline that consists of various aspects of the main skills in it. The main skill aspects include listening skills (Mahārah al-Istimā '), speaking skills (Mahārah al-Kalām), reading skills (Mahārah al-qirāʼah), and writing skills (Mahārah al-Kitābah). From these definitions it can be concluded that learning Arabic is an activity of transfer of knowledge carried out by educators towards students about Arabic with all its aspects in a particular learning environment. Today there are many expert opinions related to Arabic learning theory. There are theories that seem mutually supportive of one another, there is also the opposite, contradictory. But that is the essence of theory, nothing is eternal, if there is a new theory that proves the error of the old theory then the old one will immediately be abandoned. Theory of Behaviorism (al-sulūkiyyah) and the theory of Mentalism (al-ʽaqliyyah) are theories that contradict each other or differ in perspectives in viewing language learning processes. Behaviorism theory pioneered by Skinner holds that language learning is a matter of stimulus, response, repetition, and reward. The language learning process can take place well if the response is repeated correctly. In contrast to the theory of mentalism pioneered by Noam Chomsky. This theory holds that language learning is not only a matter of stimulus, response, repetition, and reward alone. But it needs to involve a process of reason. For Chomsky, giving external stimuli and responses is impossible to determine language behavior, which is capable of taking responsibility for language behavior is only the innate ability of individual language learners.